OPTIMIZATION OF TREATMENT OF PATIENTS WITH THERMAL INHALATION INJURY AND ITS IMPACT ON BURN DISEASE OUTCOMES - I.B, Mustafakulov; A.U, Ziyodullaev; Z.A, Juraeva (Research Focus International Scientific Journal, 2026)
Thermal inhalation injury (TII) is one of the most severe components of burn disease, significantly worsening its course and prognosis. This paper presents an analysis of clinical, laboratory, and endoscopic data from 144 patients with TII. The causes of unsatisfactory results of traditional treatment are examined and the effectiveness of improved therapeutic methods is assessed. It has been established that the use of a comprehensive treatment approach, including sanitizing fiberoptic bronchoscopy, optimized infusion therapy, and respiratory support, reduces the incidence of complications and mortality. A differentiated treatment strategy based on the severity of airway damage is a key factor in improving treatment outcomes.